Reklam İletilerinde Tüketici Davranışlarını Belirleyen Psikolojik Etmenler: Üniversitelerin Gazete Reklamları Uygulama Örneği - Aslan, Vildan (The Turkish Online Journal of Design Art and Communication, 2013)
Nowadays, great changes have been lived also in marketing field as the other fields had. The developments which had been lived together with globalization such as technological developments rapid increase of population, socio-economic changes in population, socio-economic choupes in population, have been caused the diversification of needs and wants. So the behaviour of purchasing is effected by the factors of social, cultural, pysicological that individuals hasn’t been shown homogen spesification. As a result of that diffirent purchasing activities have been occured changing from one to one. In this research, factors that affect consumer behavior, the analysis of foundation universities ads and analyzes, psychological factors determining the choice of high school seniors and college students were examined to compare with the results of the survey.
Keywords: Consumer; Tüketici; Psyclogical Factors; University; Psikolojik Faktörler; Üniversite